(untitled) (Rudarsko-geološko-naftni zbornik, 2020)
Majstorska Cesta is a historical road along Velebit Mt., NW of Sveti Rok, preserved in its original state since opening in 1832 and therefore added to the cultural heritage list of the Republic of Croatia in 2007. The road passes through sedimentary rocks ranging in age from Upper Carboniferous to Upper Paleogene, i.e. from 315 Ma until approx. 25 Ma old rocks (a time span of 290 Ma). These are mostly well exposed limestones and dolomites, sporadically clastics. Such rocks build up not only Velebit Mt., but also the entire Karst Dinarides. As such, they represent a unique natural museum important not only for the Croatian landscape, but also for all countries with shallow marine carbonates in the Mediterranean Region and wider, i.e. areas of Mexico, the Caribbean, along mountains like the Atlas, the Pyreneans, the Alps, the Carpathians, the Dinarides, the Helenides, the Pontides, the Taurides, the Iranides and the Himalayas. The most important geological feature is a section from Mali Alan Saddle to Tulove Grede Ridge. It is a continuous section along the Jurassic carbonates, typical for the Karst Dinarides, of stratigraphic period from Hettangian to Middle Tithonian (201.3-148 Ma), comprising the typical (index) fossils and complete geological rock sections, including contact between Jurassic and Triassic rocks. The authors have researched Velebit Mt. since 1962 until recent times, and thus recognize the necessity to preserve the described Jurassic rock outcrops. They describe the geology of Majstorska Cesta from Sv. Rok to Obrovac.